Effects of Traffic Congestion on Shopping Location Choice in the Greater eThekwini Region - Raymond Hawkins-Mofokeng; Tshepo Tlapana; Dennis Kasirye Ssemugooma (Profesional Muda Cendekia Publishing, 2022)
Shopping is a key function that characterizes the eThekwini Central Business District (CBD); however, the eThekwini CBD's central position as a favoured shopping center has deteriorated. The CBD's decline in dominance can be ascribed to a decrease in shopping trip frequency as a result of severe urban center traffic congestion, as well as a rise in the establishment of neighbouring shopping outlets in the city's outskirts. This research aims to investigate the impact of traffic congestion on shopping location selection in the eThekwini region. 400 participants were identified and selected using quantitative, non-probabilistic research methodologies, and convenience sampling procedures. Convenience and accessibility, tenant mix, entertainment, safety, and parking spaces are all significant qualities of a shopping area according to this study. The findings also suggest that the density of traffic congestion influences shoppers' perceptions of shopping location choices. According to the findings of this study, local authorities must analyze and combine all mitigating strategies to remove traffic congestion and restore the CBD's economic vibrancy. In the course of conducting the study, the researchers were constrained by a lack of adequate financial support and time.